The Effect of Moringa Isothiocyanate-1 on Renal Damage in Diabetic Nephropathy (Iranian Journal of Kidney Diseases, 2023)
Introduction. Diabetic nephropathy (DN) is the most common clinical complication of diabetes mellitus. Moringa isothiocyanate-1 (MIC-1) is effective in the treatment of diabetes mellitus, but its mechanism of action in DN remains obscure. This research specifically probed the role of MIC-1 in modulating renal injury in DN. Methods. Six db/m mice were assigned to control group and twelve db/db mice were randomly allocated to the db/db and db/db + MIC-1 groups. The body and kidney weights of the mice were monitored. Renal function indicators and oxidative stress-related markers were assessed by automatic biochemical analyzer and ELISA method. The pathological changes, apoptosis of renal tissues, extracellular regulated protein kinases (ERK) 1/2/ Nuclear factor erythroid2-related factor 2 (Nrf2) pathway-related markers, and the positive expressions of podocalyxin (Pod) and synaptopodin (Syn) were measured by H&E, PAS, and TUNEL staining, Western blot, and IHC assay. Results. MIC-1 reduced the body and kidney weights, and increased the kidney organ index (calculated as 100*kidney weight/ body weight) in db/db mice. In addition, MIC-1 improved renal function, kidney tissue injury, and apoptosis of db/db mice. MIC1 noticeably repressed the contents of reactive oxygen species (ROS) and malondialdehyde (MDA) and enhanced the contents of (glutathione) GSH, superoxide dismutase (SOD), and catalase (CAT) in db/db mice. At molecular level, db/db mice showed a decrease in p-ERK/ERK, Nrf2, SOD-1, heme oxygenase 1 (HO-1), and CAT and an increase in p- inhibitor kappa B alpha (IKBα) and p-Nuclear factor-kappa B (P65/P65), which were reversed when MIC-1 was administered. Furthermore, MIC-1 facilitated the positive expressions of Pod and Syn of the kidney tissues in db/db mice. Conclusion. MIC-1 reduces oxidative stress and renal injury by activating the ERK/Nrf2/HO-1 signaling and repressing the NFκB signaling in db/db mice.  DOI: 10.52547/ijkd.7515